Clarification of Safe Delivery by Iranian Experts Based on Clinical Governance: A Qualitative Study - Forozun Olfati; Saeid Asefzadeh; Nasrin Changizi; Masud Yonesian; Afsaneh Keramat (Tehran University of Medical Sciences, 2015)
Objective:To clarify the principles of a safe delivery based on Clinical Governance Criteria, as recommended by the pertinent experts. Materials and methods:The current study was part of a qualitative research conducted by content analysis method in 2013 and purposive sampling, performing 24 in-depth interviews based on semi-structured questions and analyzed using thematic content analysis. The participants in this research included midwives, obstetricians, managers, and hospital doctors. The data were under continuous consideration and comparative analysis in order to achieve data saturation. Results:The main concepts derived from interpretations of the pertinent experts include: Patient & Public involvement; Risk Management; Education; Clinical efficiency; Clinical audit; Personnel & Management. Conclusion:In a safe delivery, there is a vicious cycle of causes the elimination of which is only possible through benchmarking patterns that attend to most aspects of a safe delivery.Changes to services require utilization of appropriate change management strategies.